ANALISIS STRUKTURAL DAN MAKNA LUKISAN DINDING GUA DI SULAWESI SELATAN - Nurani, Indah Asikin (Berkala Arkeologi, 1999)
The spread of rock painting, which only developed in eastern Indonesia, raises the question of whether the bearer of this rock painting culture is different from the carrier of the culture that developed in western Indonesia. This paper tries to explain this based on rock paintings in South Sulawesi. In addition, with regard to cultural products in the form of rock paintings as one of the works of art that are full of symbols in conveying messages, it is necessary to study in more depth the meaning and message that the supporters of the culture are actually trying to convey. Is there a connection between the meaning of cave wall paintings as a medium for conveying messages and the migration?